When climate science became climate politics: British media representations of climate change in 1988 - Jaspal, Rusi; Nerlich, Brigitte (Sage, 2014)
Climate change has become a pressing environmental concern for scientists, social commentators and politicians. Previous social science research has explored media representations of climate change in various temporal and geographical contexts. Through the lens of Social Representations Theory, this article provides a detailed qualitative thematic analysis of media representations of climate change in the 1988 British broadsheet press, given that this year constitutes an important juncture in this transition of climate change from the domain of science to that of the socio-political sphere. The following themes are outlined: (i) “Climate change: a multi-faceted threat”; (ii) “Collectivisation of threat”; (iii) “Climate change and the attribution of blame”; and (iv) “Speculative solutions to a complex socio-environmental problem.” The article provides detailed empirical insights into the “starting-point” for present-day disputes concerning climate change and lays the theoretical foundations for tracking the continuities and discontinuities characterising social representations of climate change in the future.